Sustainable and Low Greenhouse Gas Emitting Rice Production in Latin America and the Caribbean: A Review on the Transition from Ideality to Reality - Chirinda, Ngonidzashe; Arenas Calle, Laura N.; Katto, María Cristina; Loaiza, Sandra; Correa, Fernando; Isthitani, Manabu; Loboguerrero Rodriguez, Ana María; Martínez Barón, Deissy; Graterol Matute, Eduardo Jose; Jaramillo, Santiago; Torres, Carlos Felipe; Arango, Miguel; et al. (MDPI, 2018)
The burgeoning demand for rice in Latin America and Caribbean (LAC) exceeds supply, resulting in a rice deficit. To overcome this challenge, rice production should be increased, albeit sustainably. However, since rice production is associated with increases in the atmospheric concentration of two greenhouse gases (GHGs), namely methane (CH4) and nitrous oxide (N2O), the challenge is on ensuring that production increases are not associated with an increase in GHG emissions and thus do not cause an increase in GHG emission intensities. Based on current understanding of drivers of CH4 and N2O production, we provide here insights on the potential climate change mitigation benefits of management and technological options (i.e., seeding, tillage, irrigation, residue management) pursued in the LAC region. Studies conducted in the LAC region show intermittent irrigation or alternate wetting and drying of rice fields to reduce CH4 emissions by 25–70% without increasing N2O emissions. Results on yield changes associated with intermittent irrigation remain inconclusive. Compared to conventional tillage, no-tillage and anticipated tillage (i.e., fall tillage) cause a 21% and 25% reduction in CH4 emissions, respectively. From existing literature, it was unambiguous that the mitigation potential of most management strategies pursued in the LAC region need to be quantified while acknowledging country-specific conditions. While breeding high yielding and low emitting rice varieties may represent the most promising and possibly sustainable approach for achieving GHG emission reductions without demanding major changes in on-farm management practices, this is rather idealistic. We contend that a more realistic approach for realizing low GHG emitting rice production systems is to focus on increasing rice yields, for obvious food security reasons, which, while not reducing absolute emissions, should translate to a reduction in GHG emission intensities. Moreover, there is need to explore creative ways of incentivizing the adoption of promising combinations of management and technological options.